Neurogenesis Potential Evaluation and Transcriptome Analysis of Fetal Hypothalamic Neural Stem/Progenitor Cells With Prenatal High Estradiol Exposure - Wang, Huihui; Zhou, Chengliang; Hou, Min; Huang, Hefeng; Sun, Yun (Frontiers in Genetics, 2021)
High maternal estradiol is reported to induce metabolic disorders by modulating hypothalamic gene expression in offspring. Since neurogenesis plays a crucial role during hypothalamus development, we explored whether prenatal high estradiol exposure (HE) affects proliferation and differentiation of fetal hypothalamic neural stem/progenitor cells (NSC/NPCs) in mice and performed RNA sequencing to identify the critical genes involved. NSC/NPCs in HE mice presented attenuated cell proliferation but increased neuronal differentiation in vitro compared with control (NC) cells. Gene set enrichment analysis of mRNA profiles indicated that genes downregulated in HE NSC/NPCs were enriched in neurogenesis-related Gene Ontology (GO) terms, while genes upregulated in HE NSC/NPCs were enriched in response to estradiol. Protein-protein interaction analysis of genes with core enrichment in GO terms of neurogenesis and response to estradiol identified 10 Hub mRNAs, among which three were potentially correlated with six differentially expressed (DE) lncRNAs based on lncRNA profiling and co-expression analysis. These findings offer important insights into developmental modifications in hypothalamic NSC/NPCs and may provide new clues for further investigation on maternal environment programmed neural development disorders.